Atropine, fentanyl and succinylcholine for non-urgent intubations in newborns. Issue 6 (22nd March 2009) - Lemyre, B; Cheng, R; Gaboury, I
Abstract : Objective: Describe intubation conditions and adverse events when using atropine fentanyl +/− succinylcholine as premedication. Design: Prospective observational study, as part of a quality improvement initiative. Setting: Two level 3 neonatal intensive care units in Ottawa, Canada Patients: 60 infants, median 27 weeks gestation, 1023 g at birth were included. Interventions: Infants received atropine, fentanyl +/− succinylcholine prior to the intubation. Succinylcholine was given for all infants ⩾34 weeks and at the discretion of the physician for those <34 weeks. Main outcome measures: The primary outcome was the number of attempts. Secondary outcomes were number of attempts and intubation conditions in infants who received and those who did not receive succinylcholine and safety. Results: The median number of attempts was 2. 91.7% had excellent or good conditions. The median number of attempts for infants who received succinylcholine was lower (1 vs 2) than those who did not. No serious adverse events were noted. 2 cases of difficult bag and mask ventilation after administration of fentanyl were noted. Conclusion: Atropine, fentanyl and succinylcholine before non-urgent intubations in newborns has led to a low number of attempts and good intubation conditions with no adverse events.